A Diagnosis of Sheehan's Syndrome: Better Late Than Never - Aakash Pandey; Sagar Mallappa Sindagi; Harshita Singh; Paridhi Singhal; Priya Bansal; Motilal Negi (Wolters Kluwer Medknow Publications, 2024)
A middle-aged woman presented with history of fatigue, low mood, swelling of limbs, and facial puffiness. On detailed history taking, she also complained of salt craving, secondary amenorrhea, and loss of libido for almost a decade. Investigations revealed pan-hypopituitarism. She was started on appropriate hormonal therapy which saw a rapid resolution of symptoms within 2 weeks. Sheehan's syndrome may have an acute presentation or chronic. The symptoms may be subtle like fatigue or overt like hypotension and syncope. A high degree of suspicion of Sheehan's syndrome is essential for its timely management, and goes a long way in preserving the quality of life.